The Influence of Leadership and Work Environment on The Performance of Employees of the Ministry of Transportation Through Work Motivation at The Class I Semarang Railway Engineering Center. - Simanjuntak, Tuana Resmin Florentina; Fajar Cahyo Utomo; Muhamad Harri (Madani Connection, 2024)
In this study, the researchers focused on examining how leadership, work environment, and work motivation affect the performance of Ministry of Transportation employees at the Semarang Class I Railway Engineering Center. They used probability sampling with a simple random sampling technique to select 137 individuals as respondents for the questionnaire. The study used descriptive research statistics and quantitative analysis to analyze the data. The results show that there is a positive and significant relationship between leadership and work environment on both work motivation and employee performance. Additionally, work motivation has a direct positive and significant impact on employee performance. The study further confirms the direct positive and significant influence of leadership and work environment on employee performance. These findings highlight the importance of effective leadership, conducive work environment, and high motivation in enhancing employee performance in the transportation sector.